1996
DOI: 10.1002/sca.1996.4950180403
|View full text |Cite
|
Sign up to set email alerts
|

The structure difference of proteins isolated on substrate with different techniques as studied by the atomic force microscope

Abstract: Summary:The height and width of proteins deposited on mica substrates were measured from cross sections of their atomic force microscope (AFM) images. The tapping mode AFM gave very stable and reproducible images for high molecular weight proteins. The following results were obtained:(1) The thickness of mono-, bi-, and trilayered purple membranes was 5.3, 10.4, and 16.0 nm, respectively. The calibration curve of z range of AFM based on the above data was linear. The deviation of the calibration curve at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Although our model may require further refinement for predicting the lateral dimension, it is not clear how accurate the lateral dimension predicted from SV analysis is because a cylinder may not correctly approximate the sedimentation or diffusion behavior of a supercoiling rod. For AFM, the heights of protein structures are consistently smaller than the expected diameters of such structures in solution (26,27). Here, we suggest that interactions with the mica surface might cause a partial collapse of the suprahelical structure, which, when combined with forces exerted by the AFM tip to compress the material (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Although our model may require further refinement for predicting the lateral dimension, it is not clear how accurate the lateral dimension predicted from SV analysis is because a cylinder may not correctly approximate the sedimentation or diffusion behavior of a supercoiling rod. For AFM, the heights of protein structures are consistently smaller than the expected diameters of such structures in solution (26,27). Here, we suggest that interactions with the mica surface might cause a partial collapse of the suprahelical structure, which, when combined with forces exerted by the AFM tip to compress the material (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…How are results obtained on TMV generalizable to other biomolecules? Size reduction in molecular height has been detected with AFM for a long time (Umemura et al, 1996). The origin of such a reduction in height has been attributed mostly to high-force when imaging and to substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Results on lysozyme and carbonic anhydrase II revealed the viscoelastic property of single proteins under indentation, but without noticing full denaturation (Radmacher et al, 1994;Afrin et al, 2005). Nevertheless, numerous studies demonstrated difficulties in obtaining accurate topography of biomolecules such as proteins (Umemura et al, 1996;Bergkvist et al, 1998;Cheung and Walker, 2008) and nucleic acids (Moreno-Herrero et al, 2003;Yang et al, 2007). To fully exploit the capacity of AFM to produce high resolution topographical surfaces of single biomolecules, as required in three-dimensional atomic reconstruction (Czajkowsky and Shao, 2009;Trinh et al, 2012;Chaves et al, 2014;He et al, 2016), it is critical to evaluate all sources of errors in topographical surface measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that a hard and highly charged mineral substrate (such as mica) creates difficulties during the adsorption of molecules on which they tend to partially denature (Umemura et al, 1996). However, softer systems for depositing molecules such as functionalized self-assembled monolayers are emerging (Lv et al, 2010).…”
Section: Discussionmentioning
confidence: 99%